Instagram Utilization in Promoting Ecotourism in Pari Village, Pantai Cermin District, Serdang Bedagai Regency - Tina, Tina; Sipayung, Lydia De Vega; Donargo, Sepdwiyana (International Journal of Economics and Management, 2024)
The tourist village of Pari, Pantai Cermin District, Serdang Bedagai Regency has ecotourism in the form of a typical pandan coconut nursery and the unique aroma of pandan. This research aims to utilize Instagram knowledge as a promotional medium in Pari Village Ecotourism, Serdang Bedagai Regency. In connection with this objective, a problem formulation can be put forward, namely how to use the Pari village ecotourism social media Instagram as a promotional medium. The research methodology used by the author in this research is descriptive with a qualitative approach. The data collection techniques used were observation, interviews, literature study, and documentation. From the results of this research, it can be concluded that the Pari Village ecotourism manager has used Instagram as a promotional medium in promoting Pari Village ecotourism. With the Instagram accounts @desawisatapari, and @hambalee_01, tourists are greatly helped in finding information. However, the obstacle experienced by Pari Village ecotourism managers is the lack of human resources in managing Pari Tourism Village Instagram. So the Pari tourism village Instagram is still not effective in promoting Pari village ecotourism in the form of pandan coconut nurseries because it is not by the promotional media indicators